The Fundamentals of the Quranic Message and its Timeless Nature - Nubail, Ahmad; Sulthani, Dinil Abrar (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2025)
This paper examines some fundamentals of the Quranic messages and elucidates their timeless nature in challenging relativism through the lens of Islamic perspectives. The issues of relativism have been spreading in all elements of social and moral construction. Moreover, the authenticity and eternity of the Quran have been questioned. Consequently, the truth of messages in the Quran also has been doubted. In other words, without exception, all ingredients in the Qur’an become nothing. In fact, people become confused with values and standards of morals, truth, religion, etc, in their daily lives. Indeed, the Quran itself has declared this book a guide of life for human beings, which is rich in permanent values and standards of morals, truth, religion, etc., but these things are unbounded by time and place. It means that the messages of the Quran are timeless in nature. Therefore, this paper investigates some problems above by presenting some verses of the Quran as a permanent solution for relativism issues.